Acid-doped ABPBI membranes prepared by low-temperature casting: Proton conductivity and water uptake properties compared with other polybenzimidazole-based membranes - Díaz, Liliana Alicia; Abuin, Graciela Carmen; Corti, Horacio Roberto (Electrochemical Society, 2016)
Fil: Díaz, Liliana Alicia. Comisión Nacional de Energía Atómica. Centro Atómico Constituyentes; Argentina. Instituto Nacional de Tecnología Industrial; Argentina